Advocacy in Practice: Women of Color and Our Allies - Brown, Paulette; Gomez, Madeline; Lee, Jin Hee; Mathai, Amreeta; Bootstaylor, Chloe (Columbia Journal of Gender and Law, 2018)
Panel moderated by Amreeta Mathai, featuring Paulette Brown, Madeline Gomez, and Jin Hee Lee. Introduced by Chloe Bootstaylor.